Catamenial Hemoptysis and Pneumothoraces in a Patient with Cystic Fibrosis - Chris M Parker; Robert Nolan; M Diane Lougheed (Canadian Respiratory Journal)
Hemoptysis or pneumothorax that recurs with the onset of menses is strongly suggestive of thoracic endometriosis syndrome (TES). TES is a rare disorder, with relatively few cases reported in the literature. A 32-year-old woman with cystic fibrosis, who over a period of several months had experienced recurrent catamenial hemoptysis and pneumothoraces, including an episode of life-threatening hemoptysis that coincided with menstruation, is presented. Thoracic computed tomography and magnetic resonance imaging scans, as well as a bronchosopic evaluation that demonstrated endobronchial lesions that disappeared after menses, support the diagnosis of TES in the present patient. The patient was treated empirically with danazol and subsequently underwent a successful double-lung transplantation. Danazol was discontinued postoperatively, and she was started on an oral contraceptive. Eighteen months post-transplant, she has not experienced a recurrence of her catamenial symptoms, despite having resumed a regular menstrual cycle.